A review of the selection process and decontamination methods with the use of face shields in UV phototherapy during the SARS‐CoV‐2 pandemic. Issue 3 (4th May 2022) - Granahan, A.; McCavana, J.; Lally, A.; Morgan, I.; Fitzgerald, S.; Moriarty, B.
Abstract: Targeted ultraviolet (UV) phototherapy has been used in the management of a wide variety of dermatological clinical conditions including moderate to severe psoriasis unresponsive to topical therapies, vitiligo, severe atopic dermatitis and lymphoproliferative disorders. To date there are no uniform, standardised guidelines for the selection and decontamination process for UV personal protective equipment (PPE) and facial shields used in phototherapy. In the current climate, Coronavirus 2019 (COVID‐19) pandemic, standards regarding all decontamination and disinfection processes are under significant scrutiny. In terms of the UV‐PPE and facial shields used in phototherapy, careful disinfection procedures need to be implemented to ensure that the decontamination practice is effective enough to neutralise the virulent virus whilst maintaining maximal protection to the user from UV‐rays and safeguard the equipment from damage during the cleaning process. The aim of this report is to provide an evidence based review of the current and international practice standards guiding the selection, use and decontamination processes of UV facial shields in phototherapy. The complications and concerns that the COVID‐19 pandemic has had on this practice is highlighted. As such, we performed a comprehensive evaluation of the literature to provide recommendations as to the most effective, time efficient and safest practices for disinfection and decontamination of UV facial shields used in phototherapy during these unprecedented times.